The impact of inter-city railway connections on urban expansion: a heterogeneous perspective based on types and regional structures - Xi Wei; Feng Zhen (npj Sustainable Mobility and Transport)
Abstract Inter-city railway infrastructure investment is crucial for urban development. Based on railway frequency data from China between 2009 and 2019, this study employs the spatial econometric model to analyze the impact of inter-city railway connections (IRC) on urban expansion. Additionally, this study conducts heterogeneity analysis by subdividing the dataset according to railway types and regional structures. We also investigate the mediating role of investment and consumption in the relationship between IRC and urban expansion. The results indicate that IRC have a positive direct impact, and a negative spatial spillover effect on urban expansion. Moreover, there are significant differences in the mechanisms of IRC across different railway types (high-speed railway and conventional railway) and regional structures (provinces, agglomerations and metropolitans). Finally, IRC can indirectly promote urban expansion by stimulating investment and consumption. Based on these findings, we propose several policy suggestions for transportation infrastructure planning of China and other developing countries.